VIEWS REGARDING THE CURRENT ADMINISTRATIVE PHENOMENON - Iulian NEDELCU; Paul-Iulian NEDELCU (Challenges of the Knowledge Society)
An essential pillar of the rule of law – the principle of legality of the administration, which together with the separation of powers in the state, must guarantee the fundamental rights and freedoms of citizens. The form of government, as a concept, we appreciate that it specifically designated the use and organisation of state bodies, as well as the characteristics, principles that underlie the relationship between them. At the same time, the economic and social structure of the state, the principles underlying the organisation and functioning of power, its objectives and forces, the way in which society is reflected in the power and style it imparts to the rulers must be taken into account. From the point of view of the forms of government, it is spoken in the specialised literature of monarchs and republics. Within the republic, we find that the position of head of state is performed by an authority that can be either unipersonal or collegial. We note, depending on the elements considered in the more general concept of state form that a number of notions and derived concepts appear, such as those of form of government, state structure and political regime. The set of institutions, methods and means by which power is realised represents the political regime, which has much more complex determinations than the relations between the powers and the way they are organised. The idea of collaboration of powers is used by the parliamentary regime, in which we find the principle of separation of powers – understanding by this, the functional autonomy especially of the legislature and the existence of specific means of mutual pressure. From the specialised literature of public law, we come to the conclusion that there is no perfect constitutional regime – an opinion that can be criticised – that falls within pre-elaborated theoretical schemes.